2021
DOI: 10.1002/2211-5463.13135
|View full text |Cite
|
Sign up to set email alerts
|

A Sandwich‐model experiment with personal response systems on epigenetics: insights into learning gain, student engagement and satisfaction

Abstract: Sandwich-model group of students  C-group: Control group of students  QUE1: Questionnaire 1 (MCQ testing learning in-class)  QUE2: Questionnaire 2 (Feedback)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Our results revealed that Sandwich teaching exerted some positive effects on thirdyear undergraduate nursing students in China and was feasible for delivering the Community Nursing Course. As demonstrated in a previous study, Sandwich teaching increased students' learning gain, engagement in learning activities, and satisfaction with teaching (Katsioudi and Kostareli, 2021).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our results revealed that Sandwich teaching exerted some positive effects on thirdyear undergraduate nursing students in China and was feasible for delivering the Community Nursing Course. As demonstrated in a previous study, Sandwich teaching increased students' learning gain, engagement in learning activities, and satisfaction with teaching (Katsioudi and Kostareli, 2021).…”
Section: Discussionsupporting
confidence: 68%
“…The significantly higher course experience score in the Sandwich teaching group implied this teaching approach may enhance students' engagement and satisfaction with the teaching of this course. A previous study provided strong evidence that Sandwich teaching enhanced not only students' engagement but also their satisfaction with teaching (Katsioudi and Kostareli, 2021 ). Moreover, students receiving Sandwich teaching were significantly satisfied with the teaching preparation, teaching process, teaching ability, and teaching outcomes in the experimental group compared to their counterparts receiving traditional teaching (Yang and Liu, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, recent reports suggest [3,4,6,10,13,17], that personal response systems help to engage students in active and self-regulated learning, and enhance their collective efficacy, satisfaction and learning achievements.…”
Section: Related Workmentioning
confidence: 99%
“…An alternative strategy is to release content on a week-by-week basis with clear instructions on what to do at each stage with links to supporting materials. Workbooks: In the traditional lecture, active learning components would have been added in, such as quizzes to test understanding and tasks or activities to consolidate learning [ 17 , 41–43 ]. Physical or digital workbooks can be produced that give the students tasks to do while watching the videos that are centred on the key learning points.…”
Section: Scaffolding the Learningmentioning
confidence: 99%